Characterization of free L- and D-amino acids in size-segregated background aerosols over the Ross Sea, Antarctica - Feltracco, Matteo; Zangrando, Roberta; Barbaro, Elena; Becagli, Silvia; Park, Ki-Tae; Vecchiato, Marco; Caiazzo, Laura; Traversi, Rita; Severi, Mirko; Barbante, Carlo; Gambaro, Andrea (Science of The Total Environment, 2023)
The study of airborne chemical markers is crucial for identifying sources of aerosols, and their atmospheric processes of transport and transformation. The investigation of free amino acids and their differentiation between the L-and D- en-antiomers are even more important to understand their sources and atmospheric fate. Aerosol samples were collected with a high-volume sampler with cascade impactor at Mario Zucchelli Station (MZS) on the coast of the Ross Sea (Antarctica) for two summer campaigns (2018/19 and 2019/20). The total mean concentration of free amino acids in PM10 was 4 +/- 2 pmol m-3 for both campaigns and most of free amino acids were distributed in fine particles. The coarse mode of airborne D-Alanine and dimethylsufoniopropionate in seawater showed a similar trend during both Antarctic campaigns. Thus, the study of D/L Ala ratio in fine, coarse and PM10 fractions indicated the microlayer as the local source. This paper demonstrated that free amino acids follow the trend of DMS and MSA release occurred in the Ross Sea, confirming their applicability as markers for phytoplankton bloom also in paleoclimatic studies.